Recent developments in male fertility evaluation, sperm cryopreservation and artificial fertilisation, and their potential application to decapod crustacean aquaculture. (6th December 2021) - Aquino, Jon Irish Legaspi; Elliott, Lisa; Zeng, Chaoshu; Paris, Damien B.B.P.
Abstract: To maximise productivity, a better understanding of the underlying causes of subfertility that lead to inferior offspring and high mortality is imperative. In decapod crustaceans, most research has focused on female reproductive performance, with little attention given to male fertility. Paternal genetic contribution is critical to both successful embryonic and post‐embryonic development. Assessment of sperm quality can be a direct method to determine male subfertility in decapods. Sperm quality parameters such as sperm concentration and morphology have traditionally been used to determine male reproductive performance, but these procedures are time‐consuming and can only assess a limited number of sperm cells and males. Alternative diagnostic biomarkers used widely in humans and other mammals could be adapted to decapod crustaceans and may be more indicative of sperm fertilisation competence and male reproductive performance. These predictive biomarkers use fluorescent cellular dyes and high‐throughput flow cytometry or computer‐assisted sperm microscopic analysis to evaluate sperm viability, mitochondrial function, acrosome reaction and DNA fragmentation. This review examines current and advanced biomarkers to evaluate sperm quality and further explores state‐of‐the‐art procedures of sperm cryopreservation (conventional vs. vitrification techniques) and artificial fertilisation in decapod crustaceans. Sperm freezing coupled with artificial fertilisation in decapods permits the long‐term storage, controlled timing and selection of individuals for reproduction. Collectively, these tools can be applied to commercial broodstock management to improve productivity and accelerate selective breeding in the crustacean aquaculture industry.